Investigating Effects of Rim and Web Thicknesses on Root Stress of Thin-rimmed Spur Gear with Symmetric Web Arrangement - Ismail Ali, Abdul Aziz; S. R., Mohd Hanafi; Daing Mohamad Nafiz, Daing Idris; M. R. M., Rejab; Mohd Hasnun Ariff, Hassan; F., Basrawi (Centre for Advanced Research on Energy (CARe), Faculty of Mechanical Engineering, Universiti Teknikal Malaysia Melaka, 2017)
Caution on the allowable root stress values need to put in consideration for thin-rimmed gears due to the thickness of rim and web. This paper used the basic AGMA equation to predict gear tooth root stresses later to be compared with FE analysis. The aim of this paper is to investigate the effects on root stress of thin-rimmed spur gear with different rim and web thicknesses. Eight sets of thin-rimmed spur gear with different rim and web thickness have been simulated in Abaqus software as FE model for further analysis. Von Misses stress values were extracted at Hofer's critical section on tensile side of second tooth in contact. From the AGMA equation shows that tooth root stress constantly increases from 468.4 MPa for solid rim to 1222.5 MPa at 4mm rim thickness when 500 Nm of load applied. While FEM result shows Von Misses stress value to become uneven at the line of Hofer's critical section when different rim and web thickness involves.